Demographic and Job Burnout Analysis on Working Mothers in Indonesia - Jeni Wulandari; Gita Paramitha Djausal; Mediya Destalia; Intan Defitasari (Jurnal Administrasi Bisnis)
Women's participation in the world of work today is quite high. This condition is a challenge for mothers to work in carrying out domestic roles and roles in their work that impact emotional and physical fatigue, as conditions termed the job burnout. In this study, specifically associating job burnout with demographic factors such as age, level of education, tenure, salary, marriage age, and the number of children, who in previous studies did not always show consistent results. As for the measurement of job burnout using the Maslach Burnout Inventory (MBI). Data collection techniques are carried out by distributing questionnaires online to 260 respondents working in Indonesia. The data were then analysed using descriptive analysis and Kruskal-Wallis analysis. The results showed differences in age, education, marriage age, and the number of children to the job burnout response. Meanwhile, there are no differences based on tenure and salary amount. Whatever the tenure and salary amount received, the job burnout response is in a fairly high to low range. The results of the study provide managerial implications in managing work situations that reduce the potential of job burnout in working mothers, as well as support for further study development in understanding the social and psychological dynamics of the mother working comprehensively.